Gestión de recaudación de tasas y su incidencia en la operatividad de la empresa pública municipal de agua potable y alcantarillado del cantón Valencia periodo 2016-2018 - Cedeño Bustamante, Iseth Paola (2020)
the investigation, an analysis of the management of collection of fees of the public drinking water and sewerage company, located in the canton of Valencia, Province of Los Ríos, the approach of the research problem was carried out by means of the question: How does it affect the management of collection of fees in the operation of the public drinking water company of the Canton of Valencia ?, for the fulfillment of this, the investigation was focused through the general objective that consisted in evaluating the collection management and its incidence in the operation of the municipal public water company in the years 2016-2018, through the research development process, information from primary sources was used, through interviews, surveys and the analysis of secondary information through inductive, deductive, descriptive analysis and synthesis with which the conclusion was reached oriented towards the authorities who are aware that e he drinking water service has improved, therefore, new collection alternatives should be considered and on the basis of this it was recommended to the authorities that they should consider expanding the collection points, through agreements with private strategic allies in order to expanding the collection system for customers, which translates into higher collection that will allow greater investment to improve the different operational phases of the vital liquid distribution system. Keywords: Management, Collection, Operation, Rates, Company, Water.